"20-MIN" OSCILLATIONS OF THE CATACLYSMIC VARIABLE TT ARI - Tremko, J.; Andronov, I. L.; Chinarova, L. L.; Kumsiashvili, M. I.; Luthardt, R.; Pajdosz, G.; Patkos, L.; Robiger, S.; Zola, S. (Одеські астрономічні публікації, 2017)
Results based on 16 nights in B, 3 in UBV and 1 in UBVRI are presented. Periodograms for detrended nightly runs showed significant peaks at different frequences from 28 to 103 c/d. Most prominent of them correspond to the best fit periods 23.7, 15.2, 27.5 and 51.6 min. Characteristics of the peaks are listed in tables. It seems that in TT Ari we observe contributions of several mechanisms of instability with similar time scales rather than a single QPO with secular decrease of the cycle.